Use of bayesian inference to correlate in vitro embryo production and in vivo fertility in Zebu Bulls - Sudano, Mateus José [UNESP]; Crespilho, André MacIel [UNESP]; Fernandes, Claudia Barbosa [UNESP]; Martins Júnior, Alicio [UNESP]; Papa, Frederico Ozanam [UNESP]; Rodrigues, Josemar; MacHado, Rui; Landim-Alvarenga, Fernanda Da Cruz [UNESP] (Hindawi, 2011)
The objective of this experiment was to test in vitro embryo production (IVP) as a tool to estimate fertility performance in zebu bulls using Bayesian inference statistics. Oocytes were matured and fertilized in vitro using sperm cells from three different Zebu bulls (V, T, and G). The three bulls presented similar results with regard to pronuclear formation and blastocyst formation rates. However, the cleavage rates were different between bulls. The estimated conception rates based on combined data of cleavage and blastocyst formation were very similar to the true conception rates observed for the same bulls after a fixed-time artificial insemination program. Moreover, even when we used cleavage rate data only or blastocyst formation data only, the estimated conception rates were still close to the true conception rates. We conclude that Bayesian inference is an effective statistical procedure to estimate in vivo bull fertility using data from IVP. © 2011 Mateus José Sudano et al.
Keywords: Bos indicus